Cleave and couple: toward fully sustainable catalytic conversion of lignocellulose to value added building blocks and fuels. Issue 56 (21st June 2018) - Sun, Zhuohua; Barta, Katalin
Abstract : Cleave and couple: sustainable catalytic pathways to value added chemicals and fuels from lignocellulose. Abstract : The structural complexity of lignocellulose offers unique opportunities for the development of entirely new, energy efficient and waste-free pathways in order to obtain valuable bio-based building blocks. Such sustainable catalytic methods – specifically tailored to address the efficient conversion of abundant renewable starting materials – are necessary to successfully compete, in the future, with fossil-based multi-step processes. In this contribution we give a summary of recent developments in this field and describe our "cleave and couple" strategy, where "cleave" refers to the catalytic deconstruction of lignocellulose to aromatic and aliphatic alcohol intermediates, and "couple" involves the development of novel, sustainable transformations for the formation of C–C and C–N bonds in order to obtain a range of attractive products from lignocellulose.